Improving childhood vaccination coverage rates: the case of fourth dose of DTaP - Sarah J. Clark; Anne E. Cowan; Katelyn Wells (Taylor & Francis Group, 2020)
Based on the most recently available national data, vaccination coverage for the combined seven-vaccine series recommended by age 24 months remains substantially below the Healthy People 2020 target of 80%. One focus for improvement is the lack of timely administration of the fourth dose of DTaP vaccine. Based on the perspective of state and local immunization program managers, key strategies include tracking immunization patterns through immunization information systems and other data sources, working with health-care providers to address challenges to timely vaccination, and developing partnerships with daycares, payers, and health systems.